Leather Balls Influence Three-Point Scores by University Basketball Players more than Synthetic or Rubber Balls Do - Gopal Kumar; Rohit Kumar Thapa (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
This study aimed to compare the influence of ball type on three-point shooting in university basketball players. Forty university basketball players were selected for the study (Mean±SD; for male subjects: age 22±1.3 years; height 1.68±0.85 m; body mass 66.4±7.1 kg; fat 10.3±2.28% and for female subjects: age 20±1.6 years; height 1.36±0.88 m; body mass 62.4±6.9 kg; fat 11.6±3.48%). A 2×3 repeated measures ANOVA revealed a significant main effect in score with ball type (F(2,76)=48.37, p<0.001, partial eta squared=0.56). Further analysis with post hoc testing revealed significant differences between synthetic and leather ball (p<0.001, d=1.27), and rubber and leather balls (p<0.001, d=1.48). No significant interaction effect of gender and ball type was found (p=0.706, partial eta squared=0.009). An independent t-test found no significant differences in three-point scores between male and female players in any ball type.